2021
DOI: 10.1186/s12967-021-02796-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of Oncuria™, a urinalysis test for bladder cancer

Abstract: Background Due to insufficient accuracy, urine-based assays currently have a limited role in the management of patients with bladder cancer. The identification of multiplex molecular signatures associated with disease has the potential to address this deficiency and to assist with accurate, non-invasive diagnosis and monitoring. Methods To evaluate the performance of Oncuria™, a multiplex immunoassay for bladder detection in voided urine samples. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Other studies have verified the predictive value of the genes used in our prediction model. CA9 can not only be used as a prognostic marker for bladder cancer [40], previous studies have shown that high CA9 expression is associated with poor prognosis of TSCC [41]. Moreover, CA9 confers resistance to ferroptosis in malignant mesothelioma under hypoxia [42].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have verified the predictive value of the genes used in our prediction model. CA9 can not only be used as a prognostic marker for bladder cancer [40], previous studies have shown that high CA9 expression is associated with poor prognosis of TSCC [41]. Moreover, CA9 confers resistance to ferroptosis in malignant mesothelioma under hypoxia [42].…”
Section: Discussionmentioning
confidence: 99%
“…The moderator took detailed notes of each encounter (quantitative and qualitative) with a focus on each participant's responses to the questions. Prior to the Zoom interview, participants were asked to read two recently published articles describing the analytical validation of Oncuria™ [4] and the clinical validation of Oncuria™ [6] to provide context to some of the questions in the clinical vignettes (Supplementary File S1). Each participant evaluated the same 9 clinical vignettes.…”
Section: Methodsmentioning
confidence: 99%
“…Initial testing in patients suspected of having BC (48 of 71 patients with BC including carcinoma in situ) resulted in a SE of 100% and SP of 92% (PPV and NPV of 97.5% and 100%, respectively). Oncuria© is a multiplex immunoassay that detects the biomarkers A1AT, APOE, ANG, CA9, IL8, MMP9, MMP10, PAI1, SDC1, and VEGFA, and also showed promising results in 46 de novo BC patients compared with non-cancer controls, with a reported SE and SP of 0.93 each and PPV and NPV of 65% and 99%, respectively [14]. However, both Uro17© and Oncuria© have not yet been evaluated in the follow-up/surveillance setting.…”
Section: Comparison With Other Testsmentioning
confidence: 99%
“…Other promising technologies include the milieu of novel markers in the urine, such as enzyme immunoassays (NMP22©; Alere, Waltham, MA, USA), H-related proteins (BTA STAT ® and BTA TRAK©; Polymedico, Cortlandt, NY, USA), immunohistochemical assays (ImmunoCyt/uCyt+©; Scimedex, Dover, NJ, USA), fluorescence in situ hybridization (UroVysion©; Abbott, Chicago, IL, USA), multiplex immunoassays (Oncuria©; Nonagen Bioscience, Jacksonville, FL, USA), oncoproteins (Uro17©; Accupath, Plainview, NY, USA), and mRNA (Cxbladder©; Pacific Edge, Hummelstown, PA, USA) [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%